A method for manufacturing a low-magnetic metal zipper tooth

CN121244995BActive Publication Date: 2026-10-23ZHEJIANG WEIXING IND DEV +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511501148.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-10-20
Publication Date
2026-10-23
Estimated Expiration
2045-10-20

AI Technical Summary

Technical Problem

[0004]目前,市场中有的不锈钢拉链均具有磁性,无法满足服装行业磁性检测的需求

Benefits of technology

(1)磁性残留降低:通过“相变抑制+磁场补偿”协同工艺,实现了无磁不锈钢拉链线材的制备,有效降低了磁性残留;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121244995B_ABST
    Figure CN121244995B_ABST
Patent Text Reader

Abstract

The present application relates to the field of clothing accessories, in particular to a preparation method of low-magnetic metal zipper teeth, which comprises the following steps: mixing Fe-based alloy powder and Y2O3 nanoparticles to obtain pre-alloy powder; then, the pre-alloy powder is made into spherical powder by plasma rotating electrode atomization method; then, the spherical powder is made into zipper tooth blank by laser selective melting process; then, the zipper tooth blank is sequentially subjected to pulse magnetic field treatment and microwave rapid annealing treatment to obtain annealed zipper teeth; finally, the annealed zipper teeth are subjected to surface modification treatment by using titanium nitride ion beam to form an amorphous-nanocrystalline composite layer on the surface of the annealed zipper teeth, thereby obtaining zipper teeth. The present application adopts a synergistic process of "phase change inhibition + magnetic field compensation", and creatively combines powder metallurgy pre-alloying and pulse magnetic field annealing technology, so that the magnetic anisotropy field, resistivity, friction coefficient can be effectively reduced, and the grain refinement effect and tensile strength can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of clothing accessories, and in particular to a method for preparing low-magnetic metal zipper teeth. Background Technology

[0002] Clothing zippers are generally classified into three types based on their materials: metal zippers, nylon zippers, and resin zippers. Metal zippers are made by pressing metal wire using a toothing machine to form the teeth. Nylon zippers are made by heating and molding nylon monofilaments around a central wire to create the teeth. Resin zippers are made from polyester plastic through injection molding. Metal zippers are particularly durable and suitable for heavy clothing such as denim and leather jackets, and are widely used.

[0003] In the manufacturing of metal zippers, metal materials are supplied to the metal zipper manufacturing equipment in the form of wires to ensure high-speed and stable production of metal zippers. Specifically, the production process of metal zippers is roughly as follows: providing metal wires → using equipment such as punch presses or die casting machines to punch or die cast the metal wires into chain teeth (or chain teeth) → making the chain belt (generally by punching or welding the chain teeth onto the back strap using a mold).

[0004] Currently, most stainless steel zippers on the market are magnetic, which cannot meet the magnetic testing requirements of the apparel industry. Specifically, conventional austenitic stainless steel wire (such as 304) undergoes a martensitic phase transformation induced by deformation after cold stamping (α' phase content >8%), resulting in a remanence of 0.05-0.1 mT, which cannot meet the requirements for use in strong magnetic field environments such as MRI (requiring <0.01 mT).

[0005] To address these issues, existing technologies have attempted to suppress phase transformation by introducing rare earth cerium (Ce) into stainless steel through microalloying. However, the addition of cerium leads to a 30% decrease in hot working plasticity, making it incompatible with continuous rolling production. Alternatively, it may only improve surface remanence while neglecting the residual microscopic magnetic domains within the material. Summary of the Invention

[0006] In view of this, the present invention provides a method for preparing low-magnetic metal zipper teeth. The preparation method of the present invention can effectively reduce magnetic anisotropy, resistivity, friction coefficient, improve grain refinement, and increase tensile strength.

[0007] This invention provides a method for preparing low-magnetic metal zipper teeth, comprising the following steps: (A) Fe-based alloy powder and Y2O3 nanoparticles are mixed to obtain pre-alloyed powder; The Fe-based alloy powder comprises, by weight percentage: Cr: 16.5%~17.2%; Ni: 4.5%~5.0%; Mn: 9.0%~10.5%; N: 0.35%~0.45%; C: ≤0.02%; The balance consists of Fe and unavoidable impurities; (B) Powder metallurgy forming: The pre-alloyed powder is atomized into spherical powder using a plasma rotating electrode atomization method; then the spherical powder is atomized into zipper tooth blanks using a laser selective melting process. (C) Two-field coupled annealing: The zipper tooth blank is subjected to pulsed magnetic field treatment and microwave rapid annealing treatment in sequence to obtain annealed zipper teeth; (D) Ion implantation surface modification: The annealed zipper teeth are surface modified using a titanium nitride ion beam to form an amorphous-nanocrystalline composite layer on the surface of the annealed zipper teeth, thus obtaining the zipper teeth.

[0008] Preferably, in step (A), the amount of Y2O3 nanoparticles added is 0.1% to 0.3% of the mass of the Fe-based alloy powder.

[0009] Preferably, in step (A), the average particle size D50 of the Y2O3 nanoparticles is 15~25nm.

[0010] Preferably, in step (B), the average particle size D50 of the spherical powder is 15~53μm, and the loose packing density is 4.5~5.0g / cm³. 3 .

[0011] Preferably, in step (B), the laser selective melting process is performed under the following conditions: laser power 200W, layer thickness 30μm, scanning speed 1000~1750mm / s, spot diameter 0.05~0.15mm, and powder feeding rate 5~30g / min.

[0012] Preferably, in step (C), the conditions for pulsed magnetic field treatment are: magnetic field strength 0.5~1.0T, frequency 5~15Hz, duration 5min, and magnetic field direction alternating with the zipper teeth at 45~90°.

[0013] Preferably, in step (C), the conditions for microwave rapid annealing are: frequency 2.45G, power 3kW, heating to 1050℃ at a heating rate of 200℃ / s, holding at the temperature, and then quenching.

[0014] Preferably, the heat preservation time is 10 seconds.

[0015] Preferably, in step (D), the surface modification treatment conditions are: ion beam energy 50 keV, dose... ions / cm².

[0016] Preferably, in step (D), the thickness of the amorphous-nanocrystalline composite layer is 5~10nm.

[0017] The preparation method provided by this invention includes: mixing Fe-based alloy powder and Y2O3 nanoparticles to obtain pre-alloyed powder; then forming spherical powder from the pre-alloyed powder using a plasma rotating electrode atomization method; then forming zipper tooth blanks from the spherical powders using a laser selective melting process; next, subjecting the zipper tooth blanks to pulsed magnetic field treatment and microwave rapid annealing treatment sequentially to obtain annealed zipper teeth; finally, performing surface modification treatment on the annealed zipper teeth using a titanium nitride ion beam to form an amorphous-nanocrystalline composite layer on the surface of the annealed zipper teeth, thus obtaining zipper teeth. This invention employs a synergistic process of "phase transformation suppression + magnetic field compensation," uniquely integrating powder metallurgy pre-alloying and pulsed magnetic field annealing technologies, which can effectively reduce magnetic anisotropy, resistivity, friction coefficient, improve grain refinement effect and tensile strength; and also reduce hot working plasticity loss.

[0018] Experimental results show that the preparation method of this invention results in a magnetic anisotropy field ΔH of the product below 50 Oe and a surface resistivity of... The strength is above Ω·cm, the coefficient of friction is below 0.12, the grain size (ASTM) reaches grade 12 or above, and the tensile strength reaches 820MPa or above. Attached Figure Description

[0019] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on the provided drawings without creative effort.

[0020] Figure 1 This is an external view of the zipper teeth obtained in Embodiment 1 of the present invention; Figure 2 This is a combined X-ray diffraction and transmission electron microscopy characterization image of the zipper tooth surface obtained in Example 1 of the present invention; wherein, Figure 2 (a) is X-ray diffraction. Figure 2 (b) is a transmission electron microscope image; Figure 3 This is a metallographic analysis diagram of the zipper tooth material obtained in Embodiment 1 of the present invention; Figure 4 This is a grain size analysis diagram of the zipper tooth material obtained in Example 1 of the present invention. Detailed Implementation

[0021] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. The terminology used herein is for the purpose of describing particular embodiments only and is not intended to be limiting of the application.

[0022] In this article, the technical features described in an open-ended manner include both closed technical solutions composed of the listed features and open technical solutions that include the listed features.

[0023] As used herein, the term "and / or" includes any and all combinations of one or more of the related listed items.

[0024] In this document, numerical ranges are referred to as continuous unless otherwise specified, and include the minimum and maximum values ​​of the range, as well as every value between the minimum and maximum values. Furthermore, when a range refers to an integer, it includes every integer between the minimum and maximum values ​​of the range. Additionally, when multiple ranges are provided to describe a feature or characteristic, the ranges may be combined. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges to which they are incorporated.

[0025] In this article, when referring to units for data ranges, if the unit is only followed by the right endpoint, it indicates that the units for the left and right endpoints are the same. For example, 15~53μm means that the units for the left endpoint "15" and the right endpoint "53" are both μm.

[0026] This invention provides a method for preparing low-magnetic metal zipper teeth, comprising the following steps: (A) Fe-based alloy powder and Y2O3 nanoparticles are mixed to obtain pre-alloyed powder; The Fe-based alloy powder comprises, by weight percentage: Cr: 16.5%~17.2%; Ni: 4.5%~5.0%; Mn: 9.0%~10.5%; N: 0.35%~0.45%; C: ≤0.02%; The balance consists of Fe and unavoidable impurities; (B) Powder metallurgy forming: The pre-alloyed powder is atomized into spherical powder using a plasma rotating electrode atomization method; then the spherical powder is atomized into zipper tooth blanks using a laser selective melting process. (C) Two-field coupled annealing: The zipper tooth blank is subjected to pulsed magnetic field treatment and microwave rapid annealing treatment in sequence to obtain annealed zipper teeth; (D) Ion implantation surface modification: The annealed zipper teeth are surface modified using a titanium nitride ion beam to form an amorphous-nanocrystalline composite layer on the surface of the annealed zipper teeth, thus obtaining the zipper teeth.

[0027] Regarding step (A) : (A) Fe-based alloy powder and Y2O3 nanoparticles are mixed to obtain pre-alloyed powder.

[0028] In this invention, the chemical composition of the Fe-based alloy powder includes: Cr: 16.5%~17.2%; Ni: 4.5%~5.0%; Mn: 9.0%~10.5%; N: 0.35%~0.45%; C: ≤0.02%; The balance consists of Fe and unavoidable impurities.

[0029] The specific content of Cr can be 16.5%, 16.6%, 16.7%, 16.8%, 16.9%, 17.0%, 17.1%, or 17.2%. The specific content of Ni can be 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, or 5.0%. The specific content of Mn can be 9.0%, 9.1%, 9.2%, 9.3%, 9.4%, 9.5%, 9.6%, 9.7%, 9.8%, 9.9%, 10.0%, 10.1%, 10.2%, 10.3%, 10.4%, or 10.5%. The specific content of N can be 0.35%, 0.36%, 0.37%, 0.38%, 0.39%, 0.40%, 0.41%, 0.42%, 0.43%, 0.44%, or 0.45%. The present invention does not impose any special restrictions on the preparation method of the Fe-based alloy powder; it can be prepared by conventional methods for preparing alloy powders in the art.

[0030] In this invention, the average particle size (D50) of the Y2O3 nanoparticles is preferably 15~25nm, specifically 15nm, 16nm, 17nm, 18nm, 19nm, 20nm, 21nm, 22nm, 23nm, 24nm, and 25nm. In this invention, the amount of Y2O3 nanoparticles added is preferably 0.1%~0.3% of the mass of the Fe-based alloy powder, specifically 0.1%, 0.2%, and 0.3%. The introduction of Y2O3 nanoparticles in this invention can produce the following effects: (1) Improve the stability of the austenitic phase: Adding... Nanoparticles can enhance the stability of the austenitic phase, making the material less prone to deformation-induced martensitic phase transformation during cold rolling; (2) suppressing magnetic domain formation: Nanoparticles are uniformly distributed at grain boundaries, which can suppress the formation and growth of magnetic domains, thereby reducing the magnetism of the material; (3) Improve material properties: The addition of [a specific ingredient] can also improve the yield strength and tensile strength of the material, resulting in better mechanical properties in the final stainless steel zipper wire.

[0031] In this invention, Fe-based alloy powder and There are no particular restrictions on the mixing method of nanoparticles; they can be mixed evenly according to conventional mixing methods in the art. After mixing, a pre-alloyed powder is obtained. This invention uses the above-mentioned pre-alloyed powder formulation, in which high manganese (Mn) replaces part of the nickel (Ni), and combined with subsequent high-pressure nitrogen atomization to prepare spherical powder, the austenitic phase stability (Md30 temperature ≤ -50℃) is improved by 40%. Simultaneously, 0.1-0.3% of [unspecified ingredient] is added. (Nano-dispersed phase) These nanoparticles will be uniformly distributed at the grain boundaries of the material in the subsequent powder metallurgy near-net-shape forming process, playing a "pinning" role and inhibiting the local magnetization caused by dislocation proliferation during cold rolling.

[0032] Regarding step (B) : (B) Powder metallurgy forming: The pre-alloyed powder is formed into spherical powder by plasma rotating electrode atomization; and the spherical powder is then formed into zipper tooth blank by laser selective melting process.

[0033] According to the present invention, the pre-alloyed powder is first prepared into spherical powder by plasma rotating electrode atomization method.

[0034] The plasma rotating electrode atomization (PREP) method is a centrifugal atomization method. A master alloy is processed into a rod, which serves as a consumable electrode. In an inert gas environment, a plasma arc is used as a heat source to heat the rotating metal rod, causing the end face to gradually melt and form a molten metal. Under centrifugal force, the molten metal is broken into droplets, which then fly out at extremely high speeds and cool and solidify into spherical powder under surface tension. In this invention, the pre-alloyed powder is used as raw material, and spherical powder is produced using the plasma rotating electrode atomization method, specifically through a plasma rotating electrode atomization device.

[0035] In this invention, the average particle size (D50) of the spherical powder is 15~53 μm, specifically 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, and 53 μm. The loose bulk density of the spherical powder is 4.5~5.0 g / cm³. 3 Specifically, it can be 4.5g / cm³. 34.6g / cm 3 4.7g / cm 3 4.8g / cm 3 4.9g / cm 3 5.0g / cm 3 .

[0036] According to the present invention, after obtaining spherical powder, the spherical powder is then processed into zipper tooth blanks by laser selective melting process.

[0037] Selective Laser Melting (SLM) is a 3D printing technology that utilizes the rapid melting and solidification of metal powder under the thermal effect of a laser beam. Specifically, this technology involves slicing and layering a 3D digital model of the part using software to obtain the contour data of each cross-section. Then, using a laser as the energy source, the laser selectively melts the metal powder layer by layer according to the contour data, following a path planned in the 3D CAD slicing model. Through layer-by-layer powder spreading, melting, solidification, and accumulation, the designed 3D solid metal part is finally obtained. In this invention, the spherical powder obtained in the previous step is used as raw material to produce a zipper tooth blank using selective laser melting, which can be achieved using selective laser melting equipment.

[0038] In this invention, the conditions of the laser selective melting process are as follows: laser power 200W, layer thickness 30μm, scanning speed 1000~1750mm / s, spot diameter 0.05~0.15mm, and powder feeding rate 5~30g / min. The scanning speed can specifically be 1000mm / s, 1100mm / s, 12000mm / s, 1300mm / s, 1400mm / s, 1500mm / s, 1600mm / s, or 1750mm / s; the spot diameter can specifically be 0.05mm, 0.06mm, 0.07mm, 0.08mm, 0.09mm, 0.10mm, 0.11mm, 0.12mm, 0.13mm, 0.14mm, or 0.15mm; and the powder feeding rate can specifically be 5g / min, 10g / min, 15g / min, 20g / min, 25g / min, or 30g / min. After laser selective melting, a zipper tooth blank is obtained.

[0039] The present invention, through the powder metallurgy near-net-shape forming method shown in step (B), can avoid stress concentration caused by traditional stamping, and the residual stress of the billet is ≤50MPa, which is 90% lower than that of cold rolling.

[0040] Regarding step (C) : (C) Dual-field coupling annealing: The zipper tooth blank is subjected to pulse magnetic field treatment and microwave rapid annealing treatment in sequence to obtain annealed zipper teeth.

[0041] Step (C) of this invention is to perform dual-field coupled annealing, the first stage being pulsed magnetic field treatment and the second stage being microwave rapid annealing treatment.

[0042] Regarding Phase One: The pulsed magnetic field treatment is a novel material surface treatment technology that utilizes a high-intensity instantaneous magnetic field to treat the material surface, altering its physical and chemical properties. In this invention, the conditions for the pulsed magnetic field treatment are: magnetic field strength 0.5~1.0T, frequency 5~15Hz, duration 5min, and the magnetic field direction alternating at 45~90° with the zipper teeth. Specifically, the magnetic field strength can be 0.5T, 0.6T, 0.7T, 0.8T, 0.9T, or 1.0T. The frequency can be 5Hz, 6Hz, 7Hz, 8Hz, 9Hz, 10Hz, 11Hz, 12Hz, 13Hz, 14Hz, or 15Hz, more preferably 10Hz. The alternating magnetic field direction with the zipper teeth, at 45~90°, can be 45°, 50°, 55°, 60°, 65°, 70°, 75°, 80°, 85°, or 90°. The aforementioned stage one employs a non-contact magnetic field generator (such as a Helmholtz coil) and is equipped with a precise control system for magnetic field strength, frequency, and direction. Through pulsed magnetic field processing, the orientation of magnetic domains is forced to randomize, thereby suppressing the α' martensite transformation.

[0043] Regarding Phase Two: In this invention, the conditions for microwave rapid annealing are: frequency 2.45 GHz, power 3 kW, heating to 1050°C at a rate of 200°C / s, followed by holding and quenching. The holding time is preferably 10 seconds. The quenching method is preferably gas quenching. The aforementioned microwave rapid annealing process utilizes an annealing chamber with an integrated microwave resonant cavity and is equipped with a non-contact temperature feedback system (infrared thermometry + AI dynamic power adjustment). This system can monitor temperature changes in real time during the annealing process and dynamically adjust the microwave power through an AI algorithm, ensuring precise control and regulation of the annealing temperature.

[0044] The present invention, through the above-mentioned dual-field coupling annealing treatment, can reduce the magnetic anisotropy coefficient (ΔH) from 1200 Oe to below 50 Oe, that is, the magnetic domain orientation is more random and the magnetic properties are more uniform; moreover, the grain size reaches ASTM12 grade (grain size ≤2μm) or above, which helps to improve the mechanical properties of the material and maintain low magnetic properties.

[0045] Regarding step (D) : (D) Surface modification by ion implantation: The annealed chain teeth are surface modified by titanium nitride ion beam to form an amorphous-nanocrystalline composite layer on the surface of the annealed chain teeth, thus obtaining zipper chain teeth.

[0046] Ion implantation surface modification refers to a technique that uses a high-energy ion beam to bombard the surface of a material, inducing atomic shifts, structural changes, or elemental doping, thereby directly altering the material's surface layer. In this invention, a titanium nitride ion beam is used to treat the surface of the annealed chain teeth. Specifically, a titanium nitride (TiN) ion beam is injected into a vacuum chamber to bombard the surface of the annealed chain teeth. In this invention, the conditions for the surface modification treatment are: ion beam energy 50 keV, dose... ions / cm².

[0047] In this invention, an amorphous-nanocrystalline composite layer is formed on the zipper tooth surface after annealing following the above-described surface modification treatment. The thickness of the amorphous-nanocrystalline composite layer is 5-10 nm, specifically 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, or 10 nm. This invention, through the above-described ion implantation surface modification treatment, can increase the surface resistivity of the zipper teeth to [a higher value]. Ω·cm, blocking micro-current corrosion and protecting the material from magnetic interference; moreover, the coefficient of friction is reduced to below 0.15, improving the smoothness of pull-in by 60%, while maintaining the low magnetism of the material.

[0048] The method for preparing low-magnetic metal zipper teeth provided by this invention employs a synergistic process of "phase transformation suppression + magnetic field compensation," uniquely integrating powder metallurgy pre-alloying and pulsed magnetic field annealing technologies. This effectively solves the problems of magnetic residue, grain boundary corrosion sensitivity, and low processing efficiency in traditional processes. It is suitable for scenarios requiring needle detection in clothing.

[0049] The present invention also provides a continuous production system for low-magnetic metal zipper teeth, comprising, in sequence: a powder supply module, a powder metallurgy forming system, a dual-field annealing module, and an ion implantation module.

[0050] The powder supply module corresponds to step (A) described above and is used to form pre-alloyed powder. The powder metallurgy forming system is used to implement step (B) described above to form the zipper tooth blank. The dual-field annealing module is used to implement step (C) described above, performing dual-field coupled annealing. The ion implantation module is used to implement step (D) described above to achieve surface modification. The dual-field annealing module includes a microwave annealing chamber, which integrates a non-contact temperature feedback system (infrared thermometry + AI dynamic power adjustment). This system can monitor temperature changes during the annealing process in real time and dynamically adjust the microwave power through an AI algorithm to ensure precise control of the annealing temperature.

[0051] In this invention, the continuous production system preferably further includes an online magnetic domain detector. The real-time scanning function of the online magnetic domain detector (based on the magneto-optical Kerr effect) can monitor the microscopic magnetic moment distribution of the zipper teeth and belt in real time, providing data support for subsequent magnetic domain adjustment.

[0052] Compared with the prior art, the present invention has the following beneficial effects: (1) Reduction of magnetic residue: Through the synergistic process of "phase change suppression + magnetic field compensation", the preparation of non-magnetic stainless steel zipper wire was realized, which effectively reduced magnetic residue; (2) Improved mechanical properties: High manganese nitrogen pre-alloyed powder is used to form a billet through plasma atomization and laser selective melting, combined with dual-field annealing and titanium nitride ion implantation treatment, so that the tensile strength of the final product is ≥800MPa, and the friction coefficient is low and the smoothness of pulling is improved. (3) Improved production efficiency: The continuous production system proposed in this invention includes powder metallurgy forming, dual-field annealing and ion implantation modules, which realizes continuous production from raw materials to finished products and improves production efficiency; (4) More uniform magnetic domain distribution: Through the real-time scanning and data analysis function of the magnetic domain detector, the micro magnetic moment distribution of the zipper teeth and the chain can be monitored in real time to ensure the uniformity of magnetic domain distribution and avoid the limitation of traditional fluxmeters that only detect surface residual magnetism.

[0053] To further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, and not for limiting the scope of the claims of the present invention.

[0054] Example 1

[0055] 1. Sample preparation

[0056] (A) Add Y2O3 nanoparticles (addition amount is 0.1%, average particle size D50 is 20nm) to Fe-based alloy powder, mix evenly, and obtain pre-alloyed powder.

[0057] The chemical composition of the Fe-based alloy powder includes: Cr 17.0%, Ni 4.5%, Mn 9.0%, N 0.35%, C 0.02%, with the balance being Fe and unavoidable impurities.

[0058] (B) Powder metallurgy forming: The pre-alloyed powder is fed into a plasma rotating electrode atomization device to form spherical powder using the plasma rotating electrode atomization method. Then, the spherical powder is fed into a laser selective melting device to form zipper tooth blanks using the laser selective melting process.

[0059] in, The spherical powder has an average particle size D50 of 20 μm and a bulk density of 4.5 g / cm³. 3 .

[0060] The conditions for the laser selective melting process are as follows: laser power 200W, layer thickness 30μm, scanning speed 1000mm / s, spot diameter 0.08mm, and powder feed rate 3g / min.

[0061] (C) Two-field coupled annealing: The zipper tooth blank is subjected to pulsed magnetic field treatment and microwave rapid annealing treatment in sequence to obtain annealed zipper teeth.

[0062] in, The conditions for pulsed magnetic field treatment are: magnetic field strength 0.8T, frequency 8Hz, duration 5min, and magnetic field direction alternating at 45° with the zipper teeth.

[0063] The conditions for microwave rapid annealing are: frequency 2.45G, power 3kW, heating rate of 200℃ / s to 1050℃, holding for 10s and then gas quenching.

[0064] (D) Ion implantation surface modification: Titanium nitride (TiN) ion beams are injected into a vacuum chamber to perform surface modification treatment on the annealed chain teeth, forming an amorphous-nanocrystalline composite layer on the surface of the annealed chain teeth, thus obtaining zipper chain teeth.

[0065] The surface modification treatment conditions are as follows: ion beam energy 50 keV, dose... The thickness of the formed amorphous-nanocrystalline composite layer is 10 nm. (ions / cm²)

[0066] 2. Sample Testing

[0067] (2.1) Appearance

[0068] The appearance of the zipper teeth obtained in Example 1 is as follows Figure 1 As shown, its surface is smooth.

[0069] (2.2) Characterization of the composite layer on the zipper tooth surface: The surface of the zipper teeth obtained in Example 1 was characterized by a combination of X-ray diffraction (XRD) and transmission electron microscopy (TEM), and the results are as follows: Figure 2 As shown, where, Figure 2 (a) is X-ray diffraction. Figure 2 (b) is a transmission electron microscope image. It can be seen that the surface layer exhibits a broadened slow scattering peak in the XRD pattern, and the TEM bright-field image shows a uniformly distributed nanocrystalline region (about 5-20 nm) interwoven with the amorphous matrix, proving that it is an amorphous / nanocrystalline composite structure.

[0070] (2.3) Metallographic structure

[0071] Metallographic analysis of the zipper teeth material obtained in Example 1 was performed, and the results are as follows: Figure 3 As shown, the non-magnetic stainless steel zipper matrix obtained by the present invention is mainly composed of austenitic structure (γ phase) with face-centered cubic crystal structure.

[0072] (2.4) Magnetic residue test and hot working plasticity loss: 1) Surface magnetic residue detection Equipment: A high-precision magnetometer (resolution 0.1mT) combined with a three-dimensional magnetic field mapping system is used to measure the magnetic field strength (1mm spacing) along the material surface in a grid pattern and draw a surface magnetic flux density distribution map.

[0073] Standard: Refer to the requirements of GB / T 3217-2013 Measurement of coercivity of permanent magnet (hard magnet) materials. The surface magnetic flux density should be ≤5mT (medical / electronic use) or ≤20mT (industrial use).

[0074] 2) Internal magnetic domain residual analysis

[0075] Technology: Combining electron backscatter diffraction (EBSD) and magnetic force microscopy (MFM), achieved through the following steps: Sample preparation: Cut a 10mm×10mm sheet along the rolling direction and electropolish until the surface is free of stress layer; EBSD scanning: Analyze grain orientation difference (GOS) and dislocation density to assess the impact of plastic deformation on magnetic domains; MFM imaging: Observing domain wall migration and residual domain distribution at the nanoscale (10 nm resolution).

[0076] Quantitative indicator: Calculate the domain remnant rate (remnant domain area / total observed area), requiring ≤3%.

[0077] See Table 1 for data comparison.

[0078] Table 1: Comparison of the effects of Example 1 and traditional process

[0079] This invention achieves a 76% reduction in surface magnetic flux density and an 83% reduction in internal magnetic domain residual rate through a multi-scale detection system, while keeping the hot working plasticity loss within 5%, thus meeting the requirements of continuous rolling production.

[0080] (2.5) Magnetic anisotropy test: Test method: 1) Hysteresis Loop Analysis (VSM) Magnetization curves in different directions (rolling, transverse, and normal) were measured using a vibrating sample magnetometer (VSM) within a magnetic field range of 0–2 T, and the magnetic anisotropy field was calculated. ).

[0081] 2) Torque magnetometer (MTS)

[0082] The torque curve was measured by rotating the sample (0~360°), and the anisotropy constant was extracted by Fourier transform. ).

[0083] 3) Results data: Example 1: ΔH was reduced from 1200 Oe in the traditional process to below 50 Oe, and the randomness of magnetic domain orientation was significantly improved.

[0084] (2.6) Surface resistivity and friction coefficient test: Test method: 1) Surface resistivity The resistance of the amorphous-nanocrystalline composite layer was measured using the four-probe method (ASTM D257 standard) at a DC voltage of 10V, and the resistivity was calculated (ρ = R×A / L, where A is the contact area and L is the spacing).

[0085] 2) Coefficient of friction

[0086] A ball-disc friction tester (ASTM G99) was used, with a load of 5 N and a sliding speed of 10 mm / s. The grinding materials were... The ball was tested 1000 times.

[0087] 3) Results data: Surface resistivity: Ω·cm (10 compared to untreated sample) 4 times).

[0088] Coefficient of friction: 0.12 (60% lower than the 0.3 of traditional metal zippers).

[0089] (2.7) Grain size and mechanical strength test: Test method: 1) Grain size According to ASTM E112 standard, grain boundary orientation difference (>15° is considered an effective grain boundary) was analyzed by electron backscatter diffraction (EBSD), and the average grain size was calculated. The analysis results are shown in the figure below. Figure 4 As shown, its grain size reaches ASTM level 12.

[0090] 2) Mechanical strength

[0091] Tensile test (ASTM E8): gauge length 25 mm, strain rate 1 mm / min, to measure tensile strength (UTS) and yield strength (YS).

[0092] 3) Results data: Grain size: ASTM 12 (grain size 1.8±0.3μm).

[0093] Tensile strength: 820 MPa, yield strength: 650 MPa (25% improvement over traditional cold rolling process).

[0094] Example 2

[0095] 1. Sample preparation

[0096] (A) Add Y2O3 nanoparticles (addition amount of 0.2%, average particle size D50 of 18nm) to Fe-based alloy powder, mix evenly, and obtain pre-alloyed powder.

[0097] The chemical composition of the Fe-based alloy powder includes: Cr 16.8%, Ni 4.8%, Mn 10.0%, N 0.40%, C 0.02%, with the balance being Fe and unavoidable impurities.

[0098] (B) Powder metallurgy forming: The pre-alloyed powder is fed into a plasma rotating electrode atomization device to form spherical powder using the plasma rotating electrode atomization method. Then, the spherical powder is fed into a laser selective melting device to form zipper tooth blanks using the laser selective melting process.

[0099] in, The spherical powder has an average particle size D50 of 35 μm and a bulk density of 4.7 g / cm³. 3 .

[0100] The conditions for the laser selective melting process are as follows: laser power 200W, layer thickness 30μm, scanning speed 1500mm / s, spot diameter 0.10mm, and powder feed rate 20g / min.

[0101] (C) Two-field coupled annealing: The zipper tooth blank is subjected to pulsed magnetic field treatment and microwave rapid annealing treatment in sequence to obtain annealed zipper teeth.

[0102] in, The conditions for pulsed magnetic field treatment are: magnetic field strength 0.8T, frequency 10Hz, duration 5min, and magnetic field direction alternating at 60° with the zipper teeth.

[0103] The conditions for microwave rapid annealing are: frequency 2.45G, power 3kW, heating rate of 200℃ / s to 1050℃, holding for 10s and then gas quenching.

[0104] (D) Ion implantation surface modification: Titanium nitride (TiN) ion beams are injected into a vacuum chamber to perform surface modification treatment on the annealed chain teeth, forming an amorphous-nanocrystalline composite layer on the surface of the annealed chain teeth, thus obtaining zipper chain teeth.

[0105] The surface modification treatment conditions are as follows: ion beam energy 50 keV, dose... The thickness of the formed amorphous-nanocrystalline composite layer is 8 nm. (ions / cm²)

[0106] 2. Sample Testing

[0107] The test was conducted according to the test method in Example 1, and the results show: Magnetic anisotropic field ΔH: 42 Oe; Surface resistivity: Ω·cm; Coefficient of friction: 0.11; Grain size: ASTM grade 13; Tensile strength: 835 MPa.

[0108] Example 3

[0109] 1. Sample preparation

[0110] (A) Add Y2O3 nanoparticles (addition amount of 0.3%, average particle size D50 of 22nm) to Fe-based alloy powder, mix evenly, and obtain pre-alloyed powder.

[0111] The chemical composition of the Fe-based alloy powder includes: Cr 17.0%, Ni 5.0%, Mn 9.5%, N 0.45%, C 0.02%, with the balance being Fe and unavoidable impurities.

[0112] (B) Powder metallurgy forming: The pre-alloyed powder is fed into a plasma rotating electrode atomization device to form spherical powder using the plasma rotating electrode atomization method. Then, the spherical powder is fed into a laser selective melting device to form zipper tooth blanks using the laser selective melting process.

[0113] in, The spherical powder has an average particle size D50 of 45 μm and a bulk density of 4.9 g / cm³. 3 .

[0114] The conditions for the laser selective melting process are as follows: laser power 200W, layer thickness 30μm, scanning speed 1750mm / s, spot diameter 0.15mm, and powder feed rate 15g / min.

[0115] (C) Two-field coupled annealing: The zipper tooth blank is subjected to pulsed magnetic field treatment and microwave rapid annealing treatment in sequence to obtain annealed zipper teeth.

[0116] in, The conditions for pulsed magnetic field treatment are: magnetic field strength 1.0T, frequency 15Hz, duration 5min, and magnetic field direction alternating at 75° with the zipper teeth.

[0117] The conditions for microwave rapid annealing are: frequency 2.45G, power 3kW, heating rate of 200℃ / s to 1050℃, holding for 10s and then gas quenching.

[0118] (D) Ion implantation surface modification: Titanium nitride (TiN) ion beams are injected into a vacuum chamber to perform surface modification treatment on the annealed chain teeth, forming an amorphous-nanocrystalline composite layer on the surface of the annealed chain teeth, thus obtaining zipper chain teeth.

[0119] The surface modification treatment conditions are as follows: ion beam energy 50 keV, dose... The thickness of the formed amorphous-nanocrystalline composite layer is 6 nm. (ions / cm²)

[0120] 2. Sample Testing

[0121] The test was conducted according to the test method in Example 1, and the results show: Magnetic anisotropy field ΔH: 38 Oe; Surface resistivity: Ω·cm; Coefficient of friction: 0.10; Grain size: ASTM grade 14; Tensile strength: 850MPa.

[0122] Comparative Example 1

[0123] Implemented according to Example 1, except that in step (C), some conditions in the pulsed magnetic field processing are adjusted to: magnetic field strength 0.3T, frequency 3Hz, and magnetic field direction alternating at 40° with the zipper teeth.

[0124] The product was tested according to the product testing method in Example 1, and the results are shown in Table 2. Table 2: Test Results of Comparative Example 1 Product

[0125] Comparative Example 1 showed that the effects of magnetic domain reforming, surface modification and grain refinement were significantly degraded because the pulse magnetic field parameters did not reach the optimized range (0.5~1.0T / 5~15Hz / 45~90°).

[0126] Comparative Example 2

[0127] Implemented according to Example 1, except that in step (C), some conditions in the pulsed magnetic field processing are adjusted to: magnetic field strength 1.5T, frequency 20Hz, and magnetic field direction alternating at 95° with the zipper teeth.

[0128] The product was tested according to the product testing method in Example 1, and the results are shown in Table 3. Table 3: Test Results of Comparative Example 2

[0129] Comparative Example 2 showed that the pulsed magnetic field parameters exceeded the optimized range (0.5~1.0T / 5~15Hz / 45~90°), resulting in reversed magnetic domain alignment, surface modification failure, and grain coarsening. Comparative Examples 1-2 demonstrate that controlling the pulsed processing parameters within a specific range is beneficial for ensuring product effectiveness.

[0130] Comparative Example 3

[0131] Implemented according to Example 1, except that in step (C), the temperature of the microwave rapid annealing process is adjusted to 1000°C.

[0132] The product was tested according to the product testing method in Example 1, and the results are shown in Table 4. Table 4: Test Results of Comparative Example 3

[0133] Comparative Example 3 showed that the microwave annealing temperature exceeded the optimized conditions (1050℃), resulting in magnetic domain disorder, surface modification failure, and severe grain coarsening.

[0134] Comparative Example 4

[0135] Implemented according to Example 1, except that in step (C), the temperature of the microwave rapid annealing process is adjusted to 1100°C.

[0136] The product was tested according to the product testing method in Example 1, and the results are shown in Table 5. Table 5: Test Results of Comparative Example 4

[0137] Comparative Example 4 showed that the microwave annealing temperature exceeded the optimized conditions (1050℃), resulting in reversed magnetic domain alignment, complete failure of surface modification, and severe grain coarsening. Comparative Examples 3-4 demonstrate that controlling specific annealing conditions is crucial to ensuring product performance.

[0138] This document uses specific examples to illustrate the principles and implementation methods of the present invention. The descriptions of these embodiments are merely to aid in understanding the method and core ideas of the present invention, including the best mode, and to enable any person skilled in the art to practice the present invention, including manufacturing and using any device or system, and implementing any combined method. It should be noted that those skilled in the art can make various improvements and modifications to the present invention without departing from its principles, and these improvements and modifications also fall within the scope of protection of the claims. The scope of protection of this patent is defined by the claims and may include other embodiments that can be conceived by those skilled in the art. If these other embodiments have structural elements similar to those expressed in the claims, or if they include equivalent structural elements that are not substantially different from those expressed in the claims, then these other embodiments should also be included within the scope of the claims.

Claims

1. A method for preparing low-magnetic metal zipper teeth, characterized in that, Includes the following steps: (A) Fe-based alloy powder and Y2O3 nanoparticles are mixed to obtain pre-alloyed powder; The Fe-based alloy powder, by mass percentage, include: Cr:16.5%~17.2%; Ni: 4.5%~5.0%; Mn: 9.0%~10.5%; N:0.35%~0.45%; C:≤0.02%; The balance consists of Fe and unavoidable impurities; (B) Powder metallurgy forming: The pre-alloyed powder is atomized into spherical powder using a plasma rotating electrode atomization method; then the spherical powder is atomized into zipper tooth blanks using a laser selective melting process. (C) Two-field coupled annealing: The zipper tooth blank is subjected to pulsed magnetic field treatment and microwave rapid annealing treatment in sequence to obtain annealed zipper teeth; The conditions for pulsed magnetic field treatment are: magnetic field strength 0.5~1.0T, frequency 5~15Hz, duration 5min, and magnetic field direction alternating with the zipper teeth at 45~90°. The conditions for microwave rapid annealing are: frequency 2.45G, power 3kW, heating to 1050℃ at a heating rate of 200℃ / s, holding at the temperature and then quenching. (D) Ion implantation surface modification: The annealed zipper teeth are surface modified using a titanium nitride ion beam to form an amorphous-nanocrystalline composite layer on the surface of the annealed zipper teeth, thus obtaining zipper teeth. The surface modification treatment conditions are: ion beam energy 50 keV, dose 1×10⁻⁶. 17 ions / cm²; The thickness of the amorphous-nanocrystalline composite layer is 5~10nm.

2. The preparation method according to claim 1, characterized in that, In step (A), the amount of Y2O3 nanoparticles added is 0.1% to 0.3% of the mass of the Fe-based alloy powder.

3. The preparation method according to claim 1, characterized in that, In step (A), the average particle size D50 of the Y2O3 nanoparticles is 15~25nm.

4. The preparation method according to claim 1, characterized in that, In step (B), the average particle size D50 of the spherical powder is 15~53μm, and the loose packing density is 4.5~5.0g / cm³. 3 .

5. The preparation method according to claim 1, characterized in that, In step (B), the conditions of the laser selective melting process are as follows: laser power 200W, layer thickness 30μm, scanning speed 1000~1750mm / s, spot diameter 0.05~0.15mm, and powder feeding rate 5~30g / min.

6. The preparation method according to claim 1, characterized in that, The heat preservation time is 10 seconds.

Citation Information

Patent Citations

  • Nano-crystal composite NdFeB permanent magnet alloy and heating processing technology for improving magnetic performance thereof

    CN101894645A

  • Heat treatment process window widening method for nanocrystalline strip with high magnetic conductivity

    CN120425134A